Two new species of the genus Loboschiza Diakonoff, 1968 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Pinkaew, Nantasak; Phosrithong, Netnapa (Zootaxa, 2018)
Two new species of Loboschiza Diakonoff, 1968 are described and illustrated from Thailand: L. bispina Phosrithong and Pinkaew, n.sp., L. rectanguluma Phosrithong and Pinkaew, n.sp. The two new species brings to 20 the number of described species in the genus, which is distributed from India to Australia.